The changing quality of stability in Europe : the Conventional Forces in Europe Treaty toward 2001 - Peters, John E., 1947- (RAND, 2000)
Some observers have wondered whether the Conventional Forces in Europe (CFE) Treaty was becoming an instrument whose purpose had become obsolete, or whose function had been taken over by other, more effective institutions. The author concludes that it no longer functions as its designers originally intended, but it nevertheless continues to contribute to the region's stability. This report illustrates that CFE cannot merely exist in stasis but must interact with other arms control activities and other European security instruments. Along the line of other security instruments, the author proposes safety and security measures to improve peoples' confidence that civil authority will function fairly to protect them--measures providing international monitors to evaluate the objectivity and legal basis of the police process, and providing people with recourse to an international court in the event due process is not observed. The protracted need for NATO forces in Bosnia is testimony to the fact that the arms control aspects of the Dayton Accords, although successful at separating the belligerents and corralling the major weapons, do not go far enough in addressing the fundamental problems of Bosnia and many parts of Europe in general.